The historical aspect of the problem of responsibility for early and forced marriages. (Journal of actual problems of jurisprudence, 2016)
The article presents a historical analysis of the criminal law on liability for infringement of human rights and freedoms in the field of marriage and family relations, pre-Soviet and Soviet period. Studying the history of the criminal law of the period shows that the criminal legal regulation was aimed at effective protection of the rights and freedoms of women and minors in the area of marriage and family relations.
Keywords: common law; the criminal code; criminal liability; coercion to marriage; compulsory marriage; kidnapping of the woman; punishment